2007
DOI: 10.1111/j.1600-0781.2007.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Twice‐ vs. thrice‐weekly MPD PUVA in psoriasis: a randomized‐controlled efficacy study

Abstract: The treatment of psoriasis patients with twice- or thrice-weekly PUVA in this study was equally effective, the number of sessions required and the cumulative doses of UVA were lower with the twice-weekly regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Of these, 670 were eliminated by reading the title or the abstract and 74 after reading the article. A total of 29 randomized controlled trials were finally selected 6–34 . The detailed flowchart describing both selection process and reasons for exclusion is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 670 were eliminated by reading the title or the abstract and 74 after reading the article. A total of 29 randomized controlled trials were finally selected 6–34 . The detailed flowchart describing both selection process and reasons for exclusion is displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the power to detect potential differences we combined the results from randomized controlled studies with those extracted from therapeutic trials in which the control arm used PUVA or NB‐UVB (Table 1) and from studies evaluating a relevant parameter (initial dose, increments…) (Table 2). A total of 18 publications concerning NB‐UVB, 6–23 and eight concerning PUVA were finally included in the analysis 24–31 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cumulative UVA dose of the twiceweekly regimen was considerably lower, 142.5 versus 241.4 J/cm 2 in the three-times weekly group. 66 A recent randomized controlled study of darker skin types proved the same in this group of patients, demonstrating that twice-weekly phototherapy maintains PUVA efficacy and may improve the riskbenefit ratio. 67 The use of maintenance PUVA is common despite limited data regarding the risks and benefits of this approach.…”
Section: Clinical Datamentioning
confidence: 90%
“…Reducing PUVA frequency to twice weekly in lightskinned patients does not compromise PUVA efficacy. [63][64][65][66] A randomized half-body controlled study of twice versus 3-times weekly PUVA involving 28 patients showed no difference in Psoriasis Area and Severity Index (PASI) score after 25 sessions, 92.9% for twice weekly and 94.8% for thrice weekly. However, the cumulative UVA dose of the twiceweekly regimen was considerably lower, 142.5 versus 241.4 J/cm 2 in the three-times weekly group.…”
Section: Clinical Datamentioning
confidence: 99%